Characterisation of promoter sequences in a Capripoxvirus genome - Fick, Wilhelmina Christina (Division of Medical Microbiology, 2017)
Capripoxviruses are of particular interest as live recombinant vectors for use in the veterinary field, since their host-range is restricted to cattle, goats and sheep. The work presented in this thesis is a preliminary study undertaken on the South African Neethling vaccine strain of lumpy skin disease virus (LSDV). As a departure point towards the eventual identification of strong promoter areas in the 143 kb genome of LSDV, a portion of its genome was cloned. Three methods for purification of LSDV DNA were compared, to determine which yielded the best quality DNA for cloning. DNA extracted directly from infected cells was excessively contaminated with bovine host-DNA, complicating the cloning of LSDV DNA. The use of pulsed field gel electrophoresis solved the contamination problem, by separating viral DNA from bovine DNA. However, insufficient amounts of viral DNA for cloning purposes, could be recovered from the gel. Sufficient amounts of good quality LSDV DNA was obtained by extraction from purified virions. Purified LSDV DNA was digested with various restriction enzymes to identify those which yielded several 4-1 0 kb fragments, for cloning into the Bluescribe plasmid transcription vector. Enrichment for large fragments (8-1 0 kb) was achieved by sucrose density centrifugation. Cloned fragments were analysed by Southern blot hybridisation to verify their viral origin. Hybridisation studies indicated that several unique regions of the LSDV genome were cloned as Pst I and Bam HI fragments respectively, i.e. the cloned fragments contained no overlapping regions. In total, 71.25 kb of the DNA of the LSDV Neethling vaccine strain has been cloned, representing approximately 50% of the viral genome. The availability of these clones now paves the way for further molecular investigations of the LSDV Neethling genome, including identification of promoter regions. A trial gene, which will be cloned and expressed in LSDV, namely the cloned VPS-gene of bluetongue virus serotype 4, was prepared and its nucleotide sequence determined. Homopolymer sequences present at the terminal ends of the gene as a result of the original cloning strategy, are known to interfere with expression and were removed by means of the polymerase chain reaction (PCR). The nucleotide sequence of the resulting PCR-tailored BTV4 VPS-genewas determined and used to deduce the amino acid sequence of the protein. The gene is 1638 bp in length and encodes a protein of 526 aa. Conserved sequences, 6 bp in length and unique to the 5'- and 3'terminal ends of all BTV genes, were detected at the termini of the tailored gene, confirming that the original clone was a full-length copy of the gene. Amplification by PCR did not mutate the open reading frame (OAF) of the gene, since it was of similar length to that reported for 5 other BTV serotypes. With a view to future investigations, including the identification of promoter sequences in the LSDV genome, a preliminary investigation of LSDV protein synthesis was undertaken, to acquire some knowledge of the growth cycle of the virus. Eighteen putative virus-specific proteins were identified by radio-labelling infected cells with [³⁵S]-methionine. By pulse-labelling infected cells with [³⁵S]methionine at various times post infection (p.i.), viral proteins were first detected at 16 hr p.i. It is, however, unlikely that the early phase of viral replication commences as late as 16 hr p.i. and these results might be attributed to various problems, such as the low multiplicity of infection used and that host protein shut-down was inefficient, thus masking the presence viral proteins. In conclusion, this investigation resulted in the cloning of 71,25 kb of the LSDV genome, the tailoring and sequencing of the BTV4 VPS gene and the identification of 18 putative LSDV proteins. This now paves the way for further research to develop LSDV as a vaccine vector.